Increasing river floods: fiction or reality?. (11th March 2015) - Blöschl, Günter; Gaál, Ladislav; Hall, Julia; Kiss, Andrea; Komma, Jürgen; Nester, Thomas; Parajka, Juraj; Perdigão, Rui A. P.; Plavcová, Lenka; Rogger, Magdalena; Salinas, José Luis; Viglione, Alberto
Abstract : There has been a surprisingly large number of major floods in the last years around the world, which suggests that floods may have increased and will continue to increase in the next decades. However, the realism of such changes is still hotly discussed in the literature. This overview article examines whether floods have changed in the past and explores the driving processes of such changes in the atmosphere, the catchments and the river system based on examples from Europe. Methods are reviewed for assessing whether floods may increase in the future. Accounting for feedbacks within the human‐water system is important when assessing flood changes over lead times of decades or centuries. It is argued that an integrated flood risk management approach is needed for dealing with future flood risk with a focus on reducing the vulnerability of the societal system. WIREs Water 2015, 2:329–344. doi: 10.1002/wat2.1079 This article is categorized under: Science of Water > Water and Environmental Change Science of Water > Water Quality